Bacterial superglue generates a full-length circumsporozoite protein virus-like particle vaccine capable of inducing high and durable antibody responses. (December 2016) - Janitzek, Christoph; Matondo, Sungwa; Thrane, Susan; Nielsen, Morten; Kavishe, Reginald; Mwakalinga, Steve; Theander, Thor; Salanti, Ali; Sander, Adam
Abstract Background Malaria, caused byPlasmodium falciparum, continues to have a devastating impact on global health, emphasizing the great need for a malaria vaccine. The circumsporozoite protein (CSP) is an attractive target for a malaria vaccine, and forms a major component of RTS, S, the most clinically advanced malaria vaccine. The clinical efficacy of RTS, S has been moderate, yet has demonstrated the viability of a CSP-based malaria vaccine. In this study, a vaccine comprised of the full-length CSP antigen presented on a virus-like particle (VLP) is produced using a split-intein conjugation system (SpyTag/SpyCatcher) and the immunogenicity is tested in mice. Methods Full-length 3d7 CSP protein was genetically fused at the C-terminus to SpyCatcher. The CSP-SpyCatcher antigen was then covalently attached (via the SpyTag/SpyCatcher interaction) toAcinetobacter phage AP205 VLPs which were modified to display one SpyTag per VLP subunit. To evaluate the VLP-display effect, the immunogenicity of the VLP vaccine was tested in mice and compared to a control vaccine containing AP205 VLPs plus unconjugated CSP. Results Full-length CSP was conjugated at high density (an average of 112 CSP molecules per VLP) to AP205 SpyTag-VLPs. Vaccination of mice with the CSP Spy-VLP vaccine resulted in significantly increased antibody titres over a course of 7 months as compared to the control group (2.6-fold higher at 7 months after immunization). Furthermore, the CSP Spy-VLP vaccine appears to stimulate production of IgG2a antibodies, which has been linked with a more efficient clearing of intracellular parasite infection. Conclusion This study demonstrates that the high-density display of CSP on SpyTag-VLPs, significantly increases the level and quality of the vaccine-induced humoral response, compared to a control vaccine consisting of soluble CSP plus AP205 VLPs. The SpyTag-VLP platform utilized in this study constitutes a versatile and rapid method to develop highly immunogenic vaccines. It might serve as a generic tool for the cost-effective development of effective VLP-vaccines, e.g., against malaria.